Donor sclera‐wrapped acrylic orbital implants following enucleation: experience in 179 patients in the Netherlands. (23rd February 2016) - Jongman, Henri P.; Marinkovic, Marina; Notting, Irene; Koetsier, Leonoor; Swart, Wouter; Schalij‐Delfos, Nicoline E.; Bleeker, Jaco; Jager, Martine J.; Luyten, Gregorius P. M.
Abstract: Purpose: To report the postoperative results after enucleation of using an acrylic orbital implant covered in donor sclera for implantation. Methods: We retrospectively analysed the charts of patients who were enucleated between 2007 and 2011. Only patients who received an acrylic implant covered with donor sclera were included. Results: A total of 179 patients were included in our analysis. About 15.6% experienced postoperative problems of which the majority were related to the position of the eyelid. Only one patient (0.6%) had an exposure of the orbital implant. Conclusion: Placing an acrylic orbital implant covered with donor sclera is a safe and effective method for reconstruction after enucleation.